The competencies of academic librarian in industrial revolution (IR 4.0) era: Perpustakaan Tun Abdul Razak (PTAR) / Nor Hidayah Othman - Othman, Nor Hidayah (2021)
This study was undertaken with the aim to explore the competency profile of an academic librarian in Industrial Revolution 4.0 (IR 4.0) era in Malaysian academic university. Problem statements, identified from review, include: (a) Industrial Revolution 4.0 (IR4.0), (b) Information & Communication Technology (ICT) & library application, (c) Issues on marketing library materials and services and (d) Issues relating education, syllabus and faculty. Knowledge, skills and attitudes have been used as a parameter and variables to define competence. The first phase of data collection involves unstructured interview with three head of librarians from Perpustakaan Tun Abdul Razak (PTAR) of UiTM Kedah, Penang and Perlis. All interview’s transcriptions were categorized to identify themes and pattern. The analysis revealed 5 main themes and 38 sub-themes which focused on knowledge, skills, attitudes, challenges, courses and type of ICT. 5 sub-themes were found to be most frequently and dominant during the interview such as Internet of Things (IoT), Web Based Integrated Library System, big data analytic, live chat with librarian and Massive Open Online Courses. In the second phase, a survey questionnaire has been applied which drew the response of 93 academic librarians from 35 PTAR’s branches of all UiTM campuses. The mean ranking and descriptive statistics were used to Analyz quantitative data. A total of 63 items which covering the elements of knowledge, skills and attitudes were tested for seeking the (i) level of knowledgeable, skillful and attitudes of competency and (ii) requirement level of knowledge, skills and attitudes of competency. Findings from a survey questionnaire indicated that knowledge (enterprises system, instructional technology and mobile technology), skills (labor, administrative, collaboration) and attitudes (community engagement, leadership, integrity) were the most knowledgeable and skillful when they performed their daily routines responsibilities. While the most required competencies that should be acquired by academic librarians of Precompiled knowledge (web technology, intellectual property, digital technologies), skills(media, communication, marketing) and attitudes (creativity, innovative, self-confidence).